Body weight and morphological profile of blood of deer (Cervus elaphus) in the conditions of Polissia Volyn - R. V. Hunchak; V. M. Hunchak; M. P. Soltys (Ukrainian Journal of Veterinary and Agricultural Sciences)
The homeostasis of the whole organism and the analysis of hematological parameters in red deer (Cervus elaphus) play an essential role in comparative physiology for health assessment and disease diagnosis. The obtained blood results can be the basis for assessing the condition of wild deer populations with an existing clinical picture or characterize the nutritional status, habitat, or other stress factors, as the hematopoietic system is susceptible to any changes in the animal body. In the course of the research, it was found that the body weight of adult deer varied depending on the population. Female deer of the Latvian and Lithuanian crossbreeds and the Eastern European population had the highest weight. As for the males, the animals of the Hungarian population had a higher weight than the English population. A high level of growth intensity in the early postnatal period was characteristic of both young females (body weight gain was in the range of 44.8–45.8 kg) and males (42.6–44.12 kg). The analysis of hematological parameters confirmed that the number of red blood cells and hemoglobin content increased in the blood of animals of the English population under technological stress (by 5.6 and 4.4 %). Regarding individual populations, it was noted that under the same conditions of immobilization of animals (medication), the number of red blood cells in the blood of Latvian crossbred deer was 8.5 % higher than the English population. The hemoglobin content was 5.3 % lower, and the saturation of red blood cells with hemoglobin was 12.9 % lower. It was found that the hematological parameters of 3–4 month-old fawns (females and males) of the English population were characterized by relative stability. Against the background of a tendency to a higher number of red blood cells in females (by 12.8 %), the hemoglobin content was 3.3 % lower than in males. The number of leukocytes in the blood of females was slightly higher than that of males, although no significant deviations were noted in some forms of white blood cells.